The Study of Industrial Nashik: - (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Nashik City is situated on the bank ofGodavari River which is originated at Sahyadri range. It’s hight from sea levelis about 565 Km. It is about 188 K.m. away from Mumbai which is capital ofMaharashtra state. Nashik is famous religious place from ancient times. Everytwle years the city celebrates Kumbmela. It is also known as Padmnagar,Trikantak, Janstan from ancient times. There are found so many proofs relatingto Roman culture.